Utilize Podcasts as Literacy and Educational Media - Meilani Dhamayanti (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
The use of digital media during the Covid-19 pandemic has helped us to continue carrying out activities and social connections during the period of activity restrictions. Podcasts are digital media used by numerous people to find various information needs. This study aims to explore the use of podcasts as learning media as well as media literacy. The method used in this paper is descriptive qualitative with in-depth interview data collection techniques for podcasters who use podcasts for literacy and educational activities. In triangulation, the researcher also interviewed the students who listened to podcasts as a medium for literacy and learning. The results of this study indicate that podcasts have benefits as a source of information for literacy and education. During the Covid-19 pandemic, podcasts are complementary to digital-based learning media such as zoom, G-meet, or MS-Team, commonly used in learning activities. Podcasts have the flexibility to be listened to in various places and situations. Podcasts are also equipped with a rewind feature to allow listeners to understand a topic better.